REVIEW ON TRAINING AND DEVELOPMENT PROGRAMM IN TELECOM SECTOR - Khan, Tanveer; Ahmed Khan, Dr. Nafees (IJRDO - Journal of Business Management, 2016)
This study analyzed the training and development process in present telecom market. In this study the company considered is Bharti Airtel. The company profile vision, goals, and company structure is reported here. This study also presents the theory and concepts of training, education, development, role of organization in training and development, role of trainee in transfer of training, methods of training, culture factor in global training program, training implementation, benefits of training and development to the company. Finally, conclusions are drawn based on the whole study.